Responses of spinothalamic tract neurons to mechanical and thermal stimuli in an experimental model of peripheral neuropathy in primates - Paleček, Jiří; Dougherty, P.M; Kim, S.H; Palečková, V; Lekan, H; Chung, J.M; Carlton, S.M; Willis, W.D (Journal of neurophysiology, 1992)
1. An experimental peripheral neuropathy (EPN) was induced in three monkeys (Macaca fascicularis) by ligation of spinal nerve L7. Behavioral responses to innocuous mechanical stimuli were tested before and after the surgery. Two weeks after the nerve ligation, the activity of spinothalamic tract (STT) neurons was recorded on both sides of the spinal cord with the animal under general anesthesia. Responses of the STT neurons to the following stimuli applied to the skin were recorded: graded mechanical stimuli (brush, press, pinch and squeeze), von Frey filaments of different bending forces (0.077-19.05 g), 5-s heat stimuli ranging from 39 to 53 degrees C, and 15 s cold stimuli (32-8 degrees C). 2. Innocuous mechanical stimulation of the foot did not evoke hindlimb withdrawal in the animals before surgery. Within 24-48 h after nerve ligation, the animals showed hindlimb withdrawal to the same innocuous stimuli. This behavior was more pronounced on the side of the ligation than on the sham-operated side and more frequent during the second week after the surgery. 3. Responses of 51 STT neurons recorded on the side of the ligation (EPN all group) were compared with responses of 33 STT cells recorded on the sham-operated side (control group) and with records from STT neurons in unoperated animals obtained earlier (reference group). Neurons from the EPN all group were divided into two sets according to their rostrocaudal location (EPN R, rostral to L6/7 border, n = 40; EPN C, caudal to L6/7 border, n = 11). 4. Neurons from the EPN all and EPN R groups had significantly higher background frequencies than those from the control and reference groups. Innocuous brush stimuli evoked mean discharge frequencies of approximately 35 Hz in EPN R neurons and only approximately 15 Hz in both control and reference groups. Increased responsiveness of EPN R neurons to innocuous stimuli was also demonstrated by lower thresholds and higher discharge frequencies to von Frey filament stimulation and by discriminative analysis of the responses evoked by graded mechanical stimuli. 5. The responses of the EPN R neurons to heat stimulation of the skin showed decreased thresholds and increased responses to suprathreshold stimuli, resulting in a significant leftward shift of the stimulus-response curve compared with both reference and control groups. The neurons from the control group showed responses comparable to reference group values. 6. Neurons from the reference group tested with the cooling stimuli showed no evoked response above background.(ABSTRACT TRUNCATED AT 400 WORDS)
Keywords: Animals; nervus ischiadicus; Sciatic Nerve; vysoká teplota; Peripheral Nervous System Diseases; Electrophysiology; Hot Temperature; Physical Stimulation; Macaca fascicularis; Neural Pathways; Cold Temperature; tractus spinothalamicus; Spinothalamic Tracts; Male; modely nemocí na zvířatech; Disease Models, Animal; nervové dráhy; elektrofyziologie; zvířata; mužské pohlaví; fyzikální stimulace; nízká teplota; nemoci periferního nervového systému